1996
DOI: 10.1159/000119300
|View full text |Cite
|
Sign up to set email alerts
|

Soporific Effect of the Neurosteroid Pregnanolone in Relation to the Substance’s Plasma Level: A Pilot Study

Abstract: The soporific effect of the neuroactive steroid pregnanolone, a metabolite of progesterone, and its relationship with plasma concentrations was assessed in 18 young, healthy, male volunteers for 2 h after administration of a single dose of pregnanolone prepared in two different formulations. Sedation was measured as sleep propensity and power increase in the low frequency delta band of the quantified EEG, based on 5-min polygraphic (EEG, EOG, EMG) recordings under resting conditions, which were performed immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In mammalian brains, steroidogenic P450s are involved in the biosynthesis of locally acting neurosteroids (Mellon et al, 2001), which accumulate in the nervous system at levels much higher than those in the blood to modulate nervous function (Schumacher et al, 1996). In the adults, neurosteroids stimulate the sensitivity of neurotransmitter receptors, which affects animal behaviors associated with these receptors (Wieland et al, 1991;Fraile et al, 1988, Schulz et al, 1996. Neurosteroids are also involved in neuronal modeling such as embryonic axonal and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian brains, steroidogenic P450s are involved in the biosynthesis of locally acting neurosteroids (Mellon et al, 2001), which accumulate in the nervous system at levels much higher than those in the blood to modulate nervous function (Schumacher et al, 1996). In the adults, neurosteroids stimulate the sensitivity of neurotransmitter receptors, which affects animal behaviors associated with these receptors (Wieland et al, 1991;Fraile et al, 1988, Schulz et al, 1996. Neurosteroids are also involved in neuronal modeling such as embryonic axonal and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone and its metabolites enhance the effects of GABA (40) and may enhance SWS. Schulz et al (39) found an increase in amplitude in the delta frequency range of the EEG in young men after administration of pregnanolone, a neuroactive metabolite of progesterone. Moldofsky et al (30), however, found a decrease in SWS in the luteal phase compared with the follicular phase that correlated with plasma progesterone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…While estrogen was found to enhance REM sleep (Schiff et al. , 1979), progesterone and its metabolite pregnanolone showed a marked sedating effect with a significant increase in NREM sleep (Schulz et al. , 1996).…”
Section: Introductionmentioning
confidence: 99%